2009
DOI: 10.1111/j.1365-2095.2008.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of waste date fruit as partial substitute for soybean meal in practical diets of juvenile Nile tilapia,Oreochromis niloticusL.

Abstract: The potential of waste date meal (WDM; low‐quality date palm, Phoenix dactylifera L.) as a carbohydrate source in formulated diets for Nile tilapia was evaluated. Four isocaloric‐practical diets (15.7 kJ g−1) were formulated incorporating WDM at 0, 100, 200 and 300 g kg−1 levels as partial substitutes for soybean meal (SBM). These were designated D0 [284 g crude protein (CP) and 383 g carbohydrate (CHO) kg−1 diet], D1 (279 g CP and 446 g CHO kg−1 diet), D2 (207 g CP and 495 g CHO kg−1 diet) and D3 (175 g CP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 49 publications
5
55
1
Order By: Relevance
“…The elevated survival rates indicate that the diets containing mango meal as a carbohydrate source did not have a harmful effect on the health of fish. The survival rate in this study was 100%, corroborating the studies of Azaza et al (2008), who observed significant difference in the survival rate of animals fed increasing levels of date meal in contrast to decreasing soybean levels in diets for tilapia. These values show that the efficiency of mango waste meal as a carbohydrate source in diets depends on the species and its eating habits.…”
Section: Resultssupporting
confidence: 80%
“…The elevated survival rates indicate that the diets containing mango meal as a carbohydrate source did not have a harmful effect on the health of fish. The survival rate in this study was 100%, corroborating the studies of Azaza et al (2008), who observed significant difference in the survival rate of animals fed increasing levels of date meal in contrast to decreasing soybean levels in diets for tilapia. These values show that the efficiency of mango waste meal as a carbohydrate source in diets depends on the species and its eating habits.…”
Section: Resultssupporting
confidence: 80%
“…Each tank was part of an open circulated system previously described by Azaza et al (2009a and2009b). The tanks were supplied with water coming from the geothermal source after undergoing cooling in a large tank of storage located at the upstream of the experimental system.…”
Section: Experimental Designmentioning
confidence: 99%
“…On the other hand, availability of quality fish feed ingredients constitutes a great challenge for fish nutritionists (Sotolu, 2010;Sotulo et al, 2011). Several studies have been investigated the potential using of date pits (Yousif et al, 1996;Osman et al, 2001;El-Sayed et al, 2006), cull dates (Srour et al, 2002;Nour et al, 2004;Azaza et al, 2008, byproducts (Sotolu and Faturoti, 2009), and feed additives (Mabrouk et al, 2008(Mabrouk et al, , 2011a in fish feeds. In addition, many of fish producers cannot afford to supplement fish diets with the highly expensive feed additives (Oladotun et al, 2003); therefore, the use of organic-based feed additives to improve feed utilization efficiency in aquaculture.…”
Section: Introductionmentioning
confidence: 99%